Eight new species of Yoyetta Moulds (Hemiptera: Cicadidae: Cicadettinae) from eastern Australia - Popple, Lindsay W. (Zootaxa, 2026)
Eight new cicada species from the eucalypt forests of eastern Australia are described in the genus Yoyetta Moulds, 2012. Yoyetta argentea sp. nov. is found in the central highlands of Queensland; Y. burwelli sp. nov. is widespread in south-eastern Queensland and also occurs in far northern New South Wales; Y. clara sp. nov. occurs in the central highlands and in inland south-eastern Queensland; Y. eastwoodi sp. nov. is found in subcoastal central and south-eastern Queensland; Y. longirostra sp. nov. is restricted to south-eastern Queensland; Y. penetrans sp. nov. is known from coastal north-eastern New South Wales; Y. wrightae sp. nov. is distributed patchily through coastal and inland south-eastern Queensland; Y. zagona sp. nov. occurs in inland southern Queensland, inland New South Wales and north-western Victoria. The new species are broadly all allied to Y. tristrigata (Goding & Froggatt) and males of all species produce simple ticking or clicking songs and generally remain inconspicuous in the canopy. Within each species a description, as well as a section on distinguishing features, distribution, habitat and behaviour, and calling song structures are provided and illustrated where available. A revised key to species for the genus Yoyetta Moulds is also provided.